RETRACTED: Resveratrol Inhibits the Migration and Metastasis of MDA-MB-231 Human Breast Cancer by Reversing TGF-β1-Induced Epithelial-Mesenchymal Transition - Sun, Yang; Zhou, Qian-Mei; Lu, Yi-Yu; Zhang, Hui; Chen, Qi-Long; Zhao, Ming; Su, Shi-Bing (Molecules (Basel, Switzerland), 2019)
Metastasis is a major cause of death in patients with breast cancer. In the process of cancer development, epithelial-mesenchymal transition (EMT) is crucial to promoting the invasion and migration of tumor cells. In a previous study, the role of resveratrol in migration and metastasis was investigated in MDA-MB-231 (MDA231) human breast cancer cells and a xenograft-bearing mouse model. Additionally, the related mechanism was explored. In the present study, in vitro Transwell assays showed that resveratrol can inhibit the migration of transforming growth factor (TGF)-β1-induced MDA231 cells in a concentration-dependent manner. An enzyme-linked immunosorbent assay (ELISA) showed that resveratrol can reduce the secretion of matrix metalloproteinase (MMP)-2 and MMP-9. Immunofluorescence was performed to confirm the expression of EMT-related markers. Immunofluorescence assays confirmed that resveratrol changed the expression of the EMT-related markers E-cadherin and vimentin. Western blot analysis demonstrated that resveratrol decreased the expression levels of MMP-2, MMP-9, Fibronectin, α-SMA, P-PI3K, P-AKT, Smad2, Smad3, P-Smad2, P-Smad3, vimentin, Snail1, and Slug, as well as increased the expression levels of E-cadherin in MDA231 cells. In vivo, resveratrol inhibited lung metastasis in a mouse model bearing MDA231 human breast cancer xenografts without marked changes in body weight or liver and kidney function. These results indicate that resveratrol inhibits the migration of MDA231 cells by reversing TGF-β1-induced EMT and inhibits the lung metastasis of MDA231 human breast cancer in a xenograft-bearing mouse model.